Parental traditional medicine use to children and its associated factors at University of Gondar Comprehensive Specialized Hospital: a cross-sectional study - Tekle, Masho Tigabe; Jara, Abdisa Gemedi; Ayenew, Mulugeta Endalamaw; Toru, Banchiamlak Zergaw; Sema, Faisel Dula (Frontiers in Public Health, 2025)
BackgroundThe use of traditional medicine (TM) among different group of population has recently shown explosive growth. However, there is limited evidence regarding the extent and its associated factors of using TM for children. This study aimed to determine the prevalence and associated factors of parental TM use for children at University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia (UOGCSH), 2023.MethodsA cross-sectional study was conducted among 401 parents who had <15 years old sick children from November 1, 2022 to April 30, 2023. The data was entered into EPI DATA software (4.6.0.2) and analyzed by SPSS version 25. Binary logistic regression was used to identify factors associated with parental TM use and reported with a 95% CI. p-value <0.05 was considered statistically significant.ResultsThe prevalence of parental TM use for children within the last 12 months was found to be 86.5% (95% CI: 82.50–90.00). Good perception of the parents on level of efficacy of TM (AOR = 3.658; 95%CI: 1.255–10.660), history of using TM for self (AOR = 3.792; 95%CI: 1.783–8.066), occupation; being housewife (AOR = 3.760; 95%CI: 1.515–9.333), daily laborer (AOR = 2.860; 95%CI: 1.035–7.908), and government employee (AOR = 4.134; 95% CI: 1.241–13.778) were significantly associated with parental TM use.ConclusionIn the present study parental TM use to children was high. Parents who had good perception on level of efficacy of TM, history of taking TM for themselves, housewife, daily laborer and government employee were more likely to use TM for their children. Thus, educating of parents about TM is essential. Further, emphasis should be given for future studies on efficacy and safety of TM use in children.